REVIEW ON RAMS ANALYSIS FOR RAILWAY VEHICLES WITH POTENTIAL APPLICATION IN RAILWAY SYSTEM OF INDONESIA - Muzakki, Sofyan; Gunawan, Leonardo; Rachman Setiawan; Kariem, M. Agus (Jurnal Rekayasa Mesin, 2024)
Railway vehicles are critical for ensuring the reliability and safety of trains, and their complexity has grown with technological advancements. RAMS analysis (Reliability, Availability, Maintainability, and Safety) has become a popular method for assessing the functional requirements of these vehicles. This review specifically investigates RAMS analysis for railway vehicles, aiming to identify trends, developments, key research challenges, and potential application in railway system of Indonesia. By thoroughly reviewing relevant articles, it explores various aspects of RAMS analysis, conducts comparative analyses, discusses potential research directions, and highlights advancements and usage in railway vehicle contexts. The methodology involves formulating research questions, searching the Scopus database for records, and applying assessment criteria to select eligible articles. Results reveal recent developments, distribution of articles, and studies focusing on reliability, availability, maintainability, and safety. This review offers valuable insights into the current state of RAMS analysis for railway vehicles and guides future research and development in this area.